PENGARUH PROFITABILITAS, LEVERAGE, INTENSITAS ASET TETAP DAN INTENSITAS PERSEDIAN TERHADAP MANAJEMEN PAJAK - -, Grace Gabena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to examine the influence of profitability, leverage, fixed asset intensity and inventory intensity on tax management. The population of this research is all Manufacturing sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. The sample in this research, which was determined based on certain characteristics, was 87 companies using a purposive sampling method from a total population of 214 companies. The data analysis technique used in this research is multiple linear regression analysis using SPSS 26 software. The results of the research show that profitability and asset intensity still influence Tax Management. Meanwhile, leverage and inventory intensity have no effect on Tax Management. Independent variabels can explain the influence of tax management by 14.8%, while the remaining 85.2% is influenced by other factors not included in this regression model.  Keyword :Profitability, Leverage, Fixed Asset Intensity, Inventory Intensity, and Tax  Managemen